Estimating global water, sanitation, and hygiene levels and related risks on human health, using global indicators data from 1990 to 2020. (5th May 2022) - Aboah, Michael; Miyittah, Michael K.
Abstract: Water quality improvement, sanitation, and hygiene have been demonstrated to have positive impacts on health, social, and economic development. However, global understanding of water quality, sanitation, and hygiene is limited. The study extracted data from the Joint Monitoring Programme (WHO/UNICEF) and the Demographic and Health Surveys (DHS) to estimate global water, sanitation, and hygiene (WASH) levels. Statistical tools of univariate and multivariate analyses were used to process global access to WASH. Results show that men (53%) had access to safe water compared to women. Women (67%), on the other hand, demonstrated better hygiene practices than men (33%). In addition, adults had access to safe water compared to children, the elderly, and strangers. Globally, there is low water quality in landlock developing countries compared to small island developing states. The categorisation of countries into economic states of low, upper-middle, and high-income countries directly affects water quality, sanitation, and hygiene. Continentally, Africa recorded the least water quality, sanitation, and hygiene levels. Thus, African countries must learn from the best practice in governmental policies and management systems from other continents regarding water improvement, sanitation, and hygiene. HIGHLIGHT: The paper seeks to meet global WASH level, reduce poverty, and hunger and protect human rights. Also, to preserve and maintain safe WASH which is critical for achieving the 2030 Agenda. Thus, poor water quality, sanitation, and hygiene affect human health, and social and economic development. Graphical Abstract